Political Regimes and External Voting Rights: A Cross-National Comparison - Umpierrez de Reguero, Sebastián A.; Yener-Roderburg, Inci Öykü; Cartagena, Vivian (Frontiers in Political Science, 2021)
In this article, we analyze the nexus between political regimes and external voting rights. Using a global longitudinal dataset, we report that higher levels of inclusion and contestation bring higher probabilities that a state adopts and implements emigrant enfranchisement. Taking outliers from our quantitative assessment, we then further examine two liberal democracies, Ireland and Uruguay, and two electoral autocracies, Turkey and Venezuela. These country cases reveal three mechanisms that shed light on the strategic role of political elites in explaining the relation between political regime type and emigrant enfranchisement. First, the democracies under study show us that in certain contexts with a relatively large diaspora size, and in which part of the political spectrum is hesitant about the political orientation of nonresident citizens, emigrant enfranchisement is neither necessarily promulgated nor implemented. Second, the autocracies illustrate that when the diaspora favors (or is perceived to favor) the incumbency, then external voting rights are extended; otherwise, third they are withheld or limited for nonresident citizens.